EVALUASI KEBIJAKAN REVITALISASI WISATA PERKAMPUNGAN BUDAYA BETAWI SETU BABAKAN JAKARTA SELATAN - Nadhifah Yasmin, Alya; Nurcahyanto, Herbasuki; Marom, Aufarul (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Efforts to develop the Betawi Cultural Village Setu Babakan Tourist Area in South Jakarta by implementing the Revitalization Policy. The revitalization policy has been in place for five years and no policy evaluation has been carried out. The aim of this research is to analyze the evaluation of revitalization policies at the Setu Babakan Betawi Cultural Village. With a descriptive qualitative research method tested through policy evaluation theory by W. Dunn including Effectiveness, Efficiency, Adequacy, Alignment, Responsiveness, and Accuracy and data collection through observation, interviews, literature study and documentation. The results of this research found that the implementation of the Setu Babakan Betawi Cultural Village area revitalization policy implemented by the Area Management Unit was going well with the results of the revitalization still being slow in development, the adequacy of facilities being poor, the distribution of information both vertically and horizontally. Based on these six indicators, things are still found that need to be improved in the formulation of the implementation of revitalization policies. The highest result based on the policy evaluation theory test using six indicators is Effectiveness, Responsiveness and Accuracy carried out by the Setu Babakan Betawi Cultural Village Management Unit in South Jakarta, namely